La estrategia de la planificación familiar implementada por el ministerio de salud pública y su impacto en la comunidad a realizarse en el subcentro de salud 4 de mayo de la ciudad de Babahoyo durante el primer semestre del 2012 - Arana Veloz, Luisa María (2012)
Family planning is a sovereign right of all people who are empowered to take decision on how many children to have and at what time, the Ministry of Public Health of Ecuador has been working tirelessly to improve the quality of life of people looking out for their rights and especially in reducing maternal mortality rates. Statistics released by the Ministry of Public Health realize that fertility levels are high in Ecuador, particularly in women of certain population groups such as indigenous women and adolescents, the lack of access and permanence in the education system are causes and consequences of the upward trend in fertility in these groups, who are more vulnerable to poverty…………